PENGARUH MANAJEMEN HUBUNGAN PELANGGAN, KUALITAS PELAYANAN, DAN KUALITAS PENGALAMAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA NASABAH PT FAC SEKURITAS INDONESIA DI YOGYAKARTA - Rizkya haris saputra; Alan Alfariza P; Rino Kurnia Efendi; Owen Al Azis Pamudya; Agus Wahyudi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
. This study aims to determine the significance of the relationship between quality and service quality Against Customer Loyalty With Customer Satisfaction As Variable Intervention At Customers PT FAC Sekuritas Indonesia in Yogyakarta. The population is a customer of PT FAC Securitas Indonesia with more than 1.5 years of PT FAC Sekuritas Indonesia. The sample is 100 customers of PT FAC Sekuritas Indonesia. The analytical technique uses several techniques supported by t test and Coefficient Determination test with the help of SPSS for windows 17.0 program. The results showed that (1) Customer Relationship Management has a negative and insignificant effect on Customer Satisfaction. (2) Quality of Service has a negative and insignificant effect on Customer Satisfaction. (3) Quality of Experience has a positive and significant impact on Customer Satisfaction. (4) Customer Satisfaction has negative and insignificant effect on Customer Loyalty. (5) Customer Relationship Management has a negative and insignificant effect on Customer Loyalty. (6) Quality of Service has a negative and insignificant influence on Customer Loyalty. (7) Quality of Experience has a positive and significant relation to Customer Loyalty.